Harnessing Rotating Heat Pipes for Passive Electric Motor Cooling: Enhancing Electric Vehicle Efficiency - Siregar, Yasmine Karenita; Rezqi, Khairu; Putra, Gerardo Janitra Puriadi; Fathoni, Andhy M; Putra, Nandy; Abral, Hairul (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
Electric vehicles are equipped with electric motors that convert electrical energy into mechanical energy to propel the vehicle. The motor experiences an increase in temperature during operation due to various losses that cause the motor temperature to rise. The performance of the electric motor will be reduced or even damaged if the heat continues to increase and the temperature exceeds 60°C. Therefore, there is a need for a cooling system that can maintain the electric motor's temperature within its working range. This study aims to investigate and test the rotating heat pipe (RHP) as a passive cooling system for electric motors. The objective of this research is to examine the performance of the RHP. The study employs a RHP with installed thermocouples on its surface. Additionally, a slip ring is utilized to serve as interface between the data acquisition module and the thermocouple sensor. In this investigation, the Rotating Heat Pipe was equipped with two slip rings to measure temperature in rotary conditions. This study proves that using RHP can reduce thermal resistance by 30-66% compared to stationary heat pipes.